The effectiveness of e-learning implementation towards students in higher learning institutions in Malacca City / Merrinie Tiong Saliong - Saliong, Merrinie Tiong (Faculty of Business and Management, 2019)
This study is aim to identify the factors that could affect the effectiveness of e-learning implementation towards students in higher learning institutions in Malacca City. It is important for higher learning institutions to provide better learning experience towards the students as it can affect the academic achievements and performance for both university and students. Thus, this present study plans to explore the reasons that can affect the effectiveness of e-learning implementation in higher learning institutions in Malacca City. Effective e-learning can help students to develop their skills in using technology as learning platform as well as give value added to them when applying for job in the future. The information for this study was gathered using primary and secondary sources. Meanwhile, convenient sampling was used to collect data from 200 respondents. The objective of this study is to measures the relationship between students’ interaction, computer efficacy and social presence with effectiveness of e-learning implementation towards students in higher learning institutions in Malacca City. The findings of this study will be measures using the Statistical Package for Social Science (SPSS) with frequency analysis, descriptive analysis, reliability analysis, Pearson correlation analysis and multiple regression analysis.